Analisis Rasio Solvabilitas Terhadap Harga Saham Pada PT. Indofarma Tbk - Nur Komalasari; M Rimawan; Aris Munandar (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Abstract. This study aims to analyze the effect of solvency ratios, proxied by Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), and Interest Coverage Ratio (ICR), on the stock price of PT Indofarma Tbk during the 2015–2024 period. This research employs a quantitative approach with an associative research design. The data used are secondary data obtained through documentation and literature study techniques from the company's annual financial statements and stock closing price data. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 22, preceded by classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that partially, DAR, DER, and ICR do not have a significant effect on the stock price of PT Indofarma Tbk. Simultaneously, these three solvency variables also do not have a significant effect on stock price, with an F-value of 1.989 and a significance level of 0.217 > 0.05. The coefficient of determination (R²) of 0.499 indicates that DAR, DER, and ICR explain 49.9% of the variation in stock prices, while the remaining 50.1% is influenced by other factors outside the research model. These findings suggest that investors do not solely consider solvency ratios when making investment decisions, but also take into account other factors such as macroeconomic conditions, company prospects, and market sentiment. Keywords: Debt to Assets Ratio, Debt to Equity Ratio, Interest Coverage Ratio, Stock Price.